Assessing Zakat Management Accountability in Semarang’s State HigherEducation Institutions: A Research Methodology - Prabowo Yudo Jayanto; Risanda A. Budiantoro (Jurnal Dinamika Akuntansi, 2024)
Purposes: The research examines the importance, accountability, and transparency of professional zakat management within State Higher Education (SHEs) in Semarang. Methods: This study employs a qualitative descriptive method with a phenomenological approach to analyze the accountability of professional zakat management in state higher education institutions in Semarang, using interviews, document analysis, and the Islamic Accountability Framework emphasizing Sharia compliance, transparency, effectiveness, and stakeholder engagement. Findings: It emphasizes the need for professional management to adhere to regulatory and institutional standards. In Semarang, UPZ UNDIP and UPZ UIN are registered with UPZ BAZNAS and comply with governance regulations. Their accountability aligns with BAZNAS standards, ensuring procedural compliance and responsive public services. However, these institutions do not fully implement PSAK 109 zakat accounting standards in their financial reporting, indicating a need for a Sharia Auditor to maintain accountability quality. Transparency remains a challenge as these institutions fail to disclose complete information. Adequate transparency establishes a perception of competence, honesty, and confidence in UPZs. The study suggests utilizing innovative digital technology to present precise information and meet the demands of the disruption era 4.0, ensuring the public can access comprehensive and transparent data. Novelty: This research bridges a novelty by focusing on professional zakat management accountability within state higher education institutions in Semarang. This focus on professionalism and the specific context can provide valuable insights for improved practices.